Formed by Algorithms: New Tasks of Christian Educators - Ezra Iskandar (Aletheia Christian Educators Journal, 2025)
Social media—TikTok, Instagram, Facebook—has become one of the most powerful formative forces among students today. It shapes not only how they communicate but also how they think, feel, and believe. What began as a tool for expression has become a system of formation that directs attention, defines identity, and distorts desire. Unfortunately, many educators fail to recognize this hidden force. Perhaps they are victims of the same habits, or they hold an uncritical optimism toward technology, or they assume that students will eventually outgrow its algorithm. In this paper I argue that Christian educators must recover a theological vision of technology grounded in the story of creation, fall, and redemption. Technology, like social media, is not neutral but spiritually formative, shaping the soul toward either worship or idolatry. The paper concludes by outlining practical implications for educators who seek to cultivate wisdom, discernment, and faithful presence in a digital age.